2020
DOI: 10.3390/buildings10070115
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Taxation on Investment Demand in the Real Estate Market: The Italian Experience

Abstract: This study investigates the effect that property taxation has on investment in the real estate market. There is a close relationship between investments in the real estate market and taxes, local communities, public policies and economic development. The analysis was developed with reference to the Italian real estate market and its tax regime. In Italy, taxation on real estate affects possession, transfers and income. These three tax rates vary according to the subjects who exchange assets and manage them, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
1
12
0
2
Order By: Relevance
“…See their paper for further discussion Chambers, Garriga, and Schlagenhauf (2009c). andCampbell and Cocco (2003) analyze mortgage choice in detail, whileLi and Yao (2007) build a model with refinancing costs 7. In a steady state where house prices are not allowed to fluctuate, equation(3)simplifies to equation(2).…”
mentioning
confidence: 99%
“…See their paper for further discussion Chambers, Garriga, and Schlagenhauf (2009c). andCampbell and Cocco (2003) analyze mortgage choice in detail, whileLi and Yao (2007) build a model with refinancing costs 7. In a steady state where house prices are not allowed to fluctuate, equation(3)simplifies to equation(2).…”
mentioning
confidence: 99%
“…The empirical analysis has shown that the impact of personal income tax on GDP is positive, as also shown by Feld and Kirchgässner (2003). Taxation also affects the investor behaviors which can be applied in the process of restarting the economy (Manganelli et al 2020). In the future, negative economic developments may require fiscal consolidation not only at the national level but also at the EU level, which is also linked to the issue of tax harmonization within the EU.…”
Section: Discussionmentioning
confidence: 96%
“…Most studies have used policies related to transaction or retention links of housing and aggregate national-scale data to assess policy implications on housing prices [56,57]. In addition, they have either framed the analysis in the context of market distortion [47,49,52,58,59], analyzing investment behavior [60,61], or cost-value analysis [62,63]. Many empirical studies have indicated that both transaction and transfer links have significant explanatory power for price differences before and after the implementation of taxes.…”
Section: Real Estate Taxes and House Pricesmentioning
confidence: 99%